2007
DOI: 10.2165/00002512-200724120-00007
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Use of Benzodiazepines or Related Drugs and Health, Physical Abilities and Cognitive Function

Abstract: Long-term use and concomitant use of more than one BZD/RD were common in elderly patients hospitalised because of acute illnesses. Long-term use was associated with daytime and night-time symptoms indicative of poorer health and potentially caused by the adverse effects of these drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
3
24
0
Order By: Relevance
“…This is in concordance with a recent Finnish study of patients aged !65 years admitted to acute hospital wards where two or more BZDs/BZDRDs were concomitantly taken by 26% of the BZDs/ BZDRDs users. This study found that use of two or more BZDs/BZDRDs was related to poorer functional abilities, impaired health status, depressive symptoms, and sleeping problems (Puustinen et al, 2007). When considering that our study population consisted of almost all Swedish elderly aged !75 years, and not only hospitalized patients, concomitant use by 19% is rather high.…”
Section: Main Findingsmentioning
confidence: 90%
See 1 more Smart Citation
“…This is in concordance with a recent Finnish study of patients aged !65 years admitted to acute hospital wards where two or more BZDs/BZDRDs were concomitantly taken by 26% of the BZDs/ BZDRDs users. This study found that use of two or more BZDs/BZDRDs was related to poorer functional abilities, impaired health status, depressive symptoms, and sleeping problems (Puustinen et al, 2007). When considering that our study population consisted of almost all Swedish elderly aged !75 years, and not only hospitalized patients, concomitant use by 19% is rather high.…”
Section: Main Findingsmentioning
confidence: 90%
“…The association with use of many other drugs and psychotropics was particularly pronounced in users of !3 BZDs/BZDRDs. Thus, elderly heavy users of BZDs/BZDRDs have a high level of medical and psychiatric co-morbidity (Puustinen et al, 2007), which may be the reason for their heavy use (Llorente et al, 2000;Bogunovic and Greenfield, 2004;Madhusoodanan and Bogunovic, 2004). Their use of BZDs/BZDRDs may need careful monitoring with respect to the total sedative load (Linjakumpu et al, 2003), with attendant impaired cognitive function (Hanlon et al, 1998).…”
Section: Main Findingsmentioning
confidence: 99%
“…Many drugs, and especially benzodiazepines, are believed to cause cognitive impairment, yet the use of these drugs appears to be widespread. Puustinen et al 1 found that ‘nearly every second patient’ in an acutely hospitalised population in Finland were taking benzodiazepines, and Paterniti et al 2 estimated that >1 million French people aged 60 years and older are chronic users. In the UK, 11.7 million prescriptions were issued for benzodiazepines in 2007 3.…”
Section: Introductionmentioning
confidence: 99%
“…Whether BZ therapy persistently affects cognitive functions has been difficult to assess. For example, Puustinen et al (2007) found no association of cognitive impairment (assessed with Mini-Mental State Examination) with long-term use of BZs in a nonrandomized study comparing patients admitted to acute hospital wards during 1 month with and without BZ treatment, whereas a small metaanalysis found significant impairments (Barker et al, 2004a). The long-term BZ effect was clearer when the reversal of cognitive impairment in different domains of neuropsychological tests was monitored during withdrawal from prolonged BZ use (Barker et al, 2004b).…”
Section: E Benzodiazepines and Other Gabaergic Drugsmentioning
confidence: 99%